Assessing the cross-country interaction of financial cycles: Evidence from a multivariate spectral analysis of the US and the UK - Till Strohsal; Proa\~no Christian R.; Jürgen Wolters (Institut für Makroökonomie und Konjunkturforschung (IMK), Hans-Böckler-Stiftung, 2017)
In recent times, a large number of studies has investigated the empirical properties of financial cycles within countries, mainly based on band-pass filter techniques. The contribution of this paper to the literature is twofold. First, in contrast to most existing studies in the financial cycle literature, we perform a multivariate parametric frequency domain analysis which takes the complete (cross-) spectrum into account and not only certain frequencies. And second, we provide evidence on the cross-country interaction of financial cycles. We focus on the US and UK and use frequency-wise Granger causality analysis as well as structural break tests to obtain three main results. The relation between cycles has recently intensified. There is a significant Granger causality from the US financial cycle to the UK financial cycle, but not the other way around. This relationship is most pronounced for cycles between 8 and 30 years. – – In jüngerer Zeit hat eine Vielzahl von Studien die empirischen Eigenschaften von Finanzzyklen, hauptsächlich mit Hilfe von Bandpassfiltertechniken, untersucht. Das vorliegende Papier trägt zu dieser Literatur in zweifacher Hinsicht bei. Erstens führen wir eine multivariate Frequenzbereichsanalyse durch, die das gesamte (Cross-) Spektrum und nicht nur einzelne Frequenzen berücksichtigt. Zweitens, liefern wir statistische Evidenz für die Interaktion von Finanzzyklen zwischen Ländern. Wir konzentrieren uns dabei auf die USA und Großbritannien. Für diese Länder führen wir Frequenz-spezifische Granger-Kausalitätsanalysen sowie Strukturtests durch, um drei wichtige Ergebnisse zu erhalten. Die Beziehung zwischen den Zyklen hat sich im Zeitverlauf verstärkt. Es gibt einen signifikanten Befund für die Granger Kausalitätswirkungsrichtung von dem US Finanzzyklus auf den Großbritanniens, nicht aber umgekehrt. Die Beziehung ist am stärksten ausgeprägt für Zyklen zwischen 8 und 30 Jahren.
urn:nbn:de:101:1-201711165255
Keywords: C32; E32; E44; 330; Financial Cycle; Vector Autoregressions; Indirect Spectrum Estimation; Coherency; Granger Causality